Antiradical and Cytoprotective Properties of Allium nutans L. Honey Against CCL4-Induced Liver Damage in Rats - Sergazy, Shynggys; Gulyayev, Alexander; Amangeldiyeva, Aidana; Nurgozhina, Ayaulym; Nurgaziyev, Madiyar; Shulgau, Zarina; Chulenbayeva, Laura; Khassenbekova, Zhanagul; Kushugulova, Almagul; Aljofan, Mohamad (Frontiers in Pharmacology, 2021)
The aim of this study is determine the in vitro and in vivo antiradical properties and the cytoprotective activity of Siberian chives honey extract. The antiradical properties of the extracts were investigated in rabbit alveolar macrophages and human foreskin fibroblast (hFFs) cells in the presence of doxorubicin, a cytotoxic substance using DPPH and ABTS assays. The cytoprotective activities were determined using 18 Wistar rats divided into 3 different groups, a negative control, and two other groups with experimentally induced hepatotoxicity by a single intraperitoneal injection of 50% carbon tetrachloride (CCl4) oil solution. A positive control group, received drinking water only and an experimental group that was treated with Siberian honey chive extracts for 7 days. In vitro treatment with Siberian honey chives extracts resulted in 78% reduction in radical activity in DPPH and 91.6% inhibition using the ABTS. Also, honey extracts were able to preserve 100% of cell viability in the presence of the cytotoxic, doxorubicin. Furthermore, the treatment with honey extracts resulted in a significant reduction in damage to the structure of liver tissue, as well significant reduction in the levels of ALT and AST in the experimental group compared to the control group.